Influence of Internet Financial Reporting, Website Information Disclosure Rate, Number of Shares Outstanding, and Sales Growth on The Frequency of Stock Trading on Manufacturing Companies on The Indonesia Stock Exchange (2015-2019) - Rivaldi Akbar; Dedy Husrizal Syah (Esensi: Jurnal Bisnis dan Manajemen, 2021)
The purpose of this study was to determine the effect of Internet Financial Reporting, Website Information Disclosure Rate, Number of Outstanding Shares, and Sales Growth on the Frequency of Stock Trading in Manufacturing Companies on the Indonesia Stock Exchange. The population of this study are manufacturing companies in 2015-2019. Sampling using purposive sampling technique. The number of samples used was 290 samples. The results of the partial study of Internet Financial Reporting do not have a significant positive effect on the frequency of stock trading. The level of Website Information Disclosure has a significant positive effect on the frequency of stock trading. The number of outstanding shares has a significant positive effect on the frequency of stock trading. Sales growth has no significant positive effect on the frequency of stock trading